Frequency of Electrolytes Abnormalities in Cirrhotic Patients Presenting with Hepatic Encepahlopathy - Khattak, Shahnawaz Yousaf; Ahmad, Nafees; Khattak, Mehmood; Mahmood, Bakhti; Abdul Quddos; Khan, Mobeen Ali (Indus Journal of Bioscience Research, 2025)
Background: Hepatic encephalopathy (HE) is a serious complication of liver cirrhosis, characterized by neuropsychiatric impairments that significantly impact patient morbidity and mortality. Electrolyte abnormalities, particularly hyponatremia and hypokalemia, are common in cirrhotic patients and are known to exacerbate HE. This study aims to determine the frequency of electrolyte abnormalities in cirrhotic patients presenting with HE and their association with clinical variables. Methods: A descriptive cross-sectional study was conducted over six months at the Department of Medicine, Khyber Teaching Hospital, Peshawar. A total of 60 cirrhotic patients with HE, aged 20–70 years, were included using non-probability sampling. Serum sodium and potassium levels were measured to identify hyponatremia (